2020
DOI: 10.1091/mbc.e20-06-0366
|View full text |Cite
|
Sign up to set email alerts
|

LIM and SH3 protein 1 localizes to the leading edge of protruding lamellipodia and regulates axon development

Abstract: The actin cytoskeleton drives cell motility and is essential for neuronal development and function. LIM and SH3 Protein 1 (LASP1) is a unique actin-binding protein that is expressed in a wide range of cells including neurons, but its roles in cellular motility and neuronal development are not well understood. We report that LASP1 is expressed in rat hippocampus early in development, and this expression is maintained through adulthood. High-resolution imaging reveals that LASP1 is selectively concentrated at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…We identified that filopodia are not the most abundant precursor but are the most efficient. Losing filopodia-initiated branches (in Plppr3 −/− neurons) appears to decrease the stability of the remaining branches, whereas a recent study has suggested that specifically losing lamellipodia results in a trend towards increased branch stability in a sample of only three neurons ( Pollitt et al, 2020 ). Furthermore, increasing filopodia-initiated branches by netrin-1 application increases the stability of branches.…”
Section: Discussionmentioning
confidence: 92%
“…We identified that filopodia are not the most abundant precursor but are the most efficient. Losing filopodia-initiated branches (in Plppr3 −/− neurons) appears to decrease the stability of the remaining branches, whereas a recent study has suggested that specifically losing lamellipodia results in a trend towards increased branch stability in a sample of only three neurons ( Pollitt et al, 2020 ). Furthermore, increasing filopodia-initiated branches by netrin-1 application increases the stability of branches.…”
Section: Discussionmentioning
confidence: 92%
“…We identified that filopodia are not the most abundant precursor, but the most efficient. Losing filopodia branches (in Plppr3 -/neurons) appears to decrease the stability of the remaining branches, while a recent study suggested that specifically losing lamellipodia trended towards increased branch stability in a sample of only three neurons (Pollitt et al, 2020). Both treatments appear to shift the equilibrium of branch precursor types, without affecting the stability of branches from each individual precursor.…”
Section: Branch Precursor Types Initiate Distinct Branching Systemsmentioning
confidence: 85%
“…This KEGG pathway was enriched in upregulated genes, which revealed the importance of the cell cycle regulation and the replication process in paralarvae feed on M diet. Similarly, LIM and SH3 domain protein 1, a protein involved in neuronal differentiation and development (Phillips et al, 2004;Myers et al, 2020;Pollitt et al, 2020), and the PREDICTED: SAFB-like transcription modulator isoform X1, an RNA-DNA-binding protein, which plays crucial roles in DNA repair, processing of mRNA and regulatory RNA, and in the interaction with chromatin-modifying complexes (Norman et al, 2016), were also upregulated. Altogether, overrepresentation of these genes and proteins showed that a proper development and correct growth were occurring in paralarvae fed on M diet.…”
Section: Discussionmentioning
confidence: 99%